VEXAS syndrome: a Swiss national retrospective cohort study (Swiss Medical Weekly, 2024)
STUDY AIMS: VEXAS syndrome is a recently discovered monogenic auto-inflammatory disease caused by a somatic mutation in the UBA1 gene that manifests with rheumatologic and haematologic features. In this report, we present the first Swiss cohort, detailing its manifestations and treatment outcomes among Swiss patients.METHODS: Data were retrospectively collected from nine hospitals across Switzerland, representing a broad geographic distribution. Treating physicians completed a standardised case report form for each patient. The principal investigator and the co-investigators collected and analysed all case report forms.RESULTS: We identified 23 patients between July 2022 and 2023, of which 17 are described. All were male. They presented with skin manifestations (88%), general symptoms (82%), venous thromboembolism (59%), ocular manifestation (59%), lung infiltrates (59%) and articular manifestations (47%). Central nervous system and kidney manifestations were very rare, and heart and digestive manifestations were absent. Macrocytic anaemia was present in all patients throughout the disease progression but only in two-thirds of patients (12/17, 71%) at the time of diagnosis. Clinical response was reached in all cases treated with ruxolitinib (4/4, 100%), upadacitinib (1/1, 100%), azacytidine (5/5, 100%) and haematopoietic stem cell transplantation (2/2, 100%). All deaths were attributed to infections (5/5, 100%).CONCLUSION: This study corroborates the clinical spectrum of VEXAS syndrome described in other cohorts. It suggests that VEXAS syndrome is not limited to patients with macrocytic anaemia. In this study, azacytidine has been used effectively among patients with myelodysplastic syndrome. In addition, Janus kinase (JAK) inhibitors, particularly ruxolitinib, have been successfully used even in those without myelodysplastic syndrome. We report two successful treatments by haematopoietic stem cell transplantation.